IMPLIKASI ADANYA PEMALSUAN TANDA TANGAN DALAM AKTA JUAL BELI TANAH YANG DILAKUKAN OLEH PPAT - Edi Asrofin; Umar Ma’ruf (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2017)
Not a few cases of falsified data that ends in the dispute often surfaced, both in print and electronic media and even non-publicized too much. Maybe in the short term, buyers do not face a lawsuit from another party, but in the long run the buyer will experience a lawsuit from another party who feels the rights to his land. Having a legal defect in a deed may result in the illegality of a later act of law. The problem of this thesis: why can there be counterfeiting of signatures in the deed of sale and purchase of land done by PPAT, how the process of handling the existence of signature falsification in the deed of sale and purchase of land done by PPAT and whether the implication of signature falsification of deed of sale and purchase of land done By PPAT.The method used in this research is sociological juridical, specification of jurisdiction approach of analysis, data used primary data and secondary data. Problems are analyzed with the theory of legal protection and legal certainty.The result of thesis research is known that the factors causing forgery of signatures in the deed of buying and selling of land conducted by PPAT PPAT have falsified the seller's signature in the process of making the Deed of Sale and Purchase, this is because PPAT assume that there has been signature from the seller in Receipt of previous buying and selling transaction so that it does not matter if in the Sale and Purchase Deed of the seller's signature in fake., The process of handling the signature fraud in the deed of sale and purchase of land conducted by PPAT is based on report from the seller who sued because felt the sign of the ladder in Fake in the Deed of Sale and Purchase, then the police conduct an investigation to the PPAT. The implication of counterfeiting the signatures of the land sale and purchase certificate conducted by PPAT may be criminalized, if it can be proven in court and Sanctions that could threaten PPAT which makes the deed inappropriate or indicated by the signature falsification in the document deed which is actually dismissal sanction with disrespect From his post. Keywords: Counterfeiting, Signature, PPAT Batang